The prevalence of gestational diabetes mellitus and its related risk factors using one-step method in Kermanshah, 2016 - Mehrali Rahimi; Fariba Karami Moghadam (Mashhad University of Medical Sciences, 2017)
Introduction: Gestational diabetes is the most common medical problem in pregnancy. According to several differences in the prevalence of gestational diabetes mellitus and its risk factors and performing a study in this regard by two-step method in Kermanshah in 2008, this study was done with aim to determine the prevalence of gestational diabetes mellitus and its related risk factors by one-step method. Methods: This cross-sectional study was performed on 1272 pregnant women at 24 to 28 weeks of gestational age referred to Kermanshah health centers in 2016. The gestational diabetes screening test (OGTT) was carried out by new one-step method for all the women. Information on risk factors in pregnant women with gestational diabetes included: history of stillbirth, miscarriage, fetal macrosomia and others and were collected in diabetes research center. Data analysis was performed using Stata software (version 11) and using t-test and logistic regression. PResults: The mean age of subjects was 27.97±5.73 years. The prevalence of gestational diabetes mellitus was obtained 8.81%. The prevalence of GDM in people without risk factors was 6.49%, in patients with one risk factor was 17.43% and those with more than one risk factor was 21.62%. With one year increase of age, the odds of gestational diabetes increased 6% and with one unit increase of BMI, the odds increased 9%. The risk of gestational diabetes in those who had history of gestational diabetes was 7.25 times and in those who had abortion was 2.44 times than those who had no history of abortion. Conclusion: Due to the involvement of variables such as age, BMI, history of gestational diabetes and history of abortion in gestational diabetes, training in people with overweight and obesity, old age and people with history of morbidity can be effective to reduce the incidence of gestational diabetes.